Project Governance: A Need for Public Sector Infrastructure Projects in Pakistan - M., Waris; Asadullah, Khan; Ishak, Ismail; Panda, Sitansu (Universiti Malaysia Pahang, 2017)

(untitled)
Infrastructure projects in developing countries have been criticized for cost overrun, delay, substandard construction works, ineffectiveness and low efficiency. In this regard, project governance approach offers a structured mechanism to detect and address all these inherent risks in a timely manner. This study has tried to review the academic literature relating to the need of project governance on infrastructure projects in order to assess the potential causes of success and failure of projects. The review is further elaborated by discussing a case study, which represents an example of ill planning of infrastructural development projects in Northern region of Pakistan. This study suggests need for exploring potential applications of project governance practices in private and public sector of developing countries.